Realidades de las ONGD y de los medios de información: en busca de un punto de encuentro - González Llamazares, Mónica (Revista Española de Desarrollo y Cooperación, 2023)
This article intends to analyze how NGOs for development can reach to be information source of media through their communication departments. It will also show a complete scene of the NGOs for development. Like this, the article tries to deepen the possibilities of communication for development.